Characterization of dropout in Business Administration at the Federal University of Jequitinhonha and Mucuri Valleys - Campus do Mucuri, between 2014 and 2018 (Research, Society and Development, 2020)
School dropout is a phenomenon characterized by the dropout of students in higher education. This means that these, when for any reason, dropout graduation is considered evaded. This paper aimed to characterize and investigate the causes of dropout in Business Administration. It is a descriptive research, made by data collection, to describe a certain phenomenon, and of a qualitative and quantitative nature, in which interviews were conducted to identify the causes and analyze the dropout percentages presented by the reports of the Academic Registration and Control Board, to present the behavior of the phenomenon. In the data analysis it was observed that the dropout rate was 38% (thirty-eight percent) and, of these, the largest number of dropouts were men, who attended high school in a public school in the municipality of Teófilo Otoni. Before being dismissed, 44% (forty-four percent) of enrollments were active for a period longer than five years, demonstrating a persistent dropout to complete the graduation initiated. It was observed that the main reasons were the adequacy of the curriculum and evaluation system of the federal higher education institution, the difficulty of interaction with teachers and the need for prior leveling to be able to follow the studies of undergraduate subjects. Thus, it is important for the institution to observe these points with its teachers, formulate a new way of interacting and evaluating its students so that they adapt to the undergraduate degree and are able to complete the course.